(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study investigates the effectiveness of targeted pedagogical interventions in enhancing Multiple-Choice Question accuracy among B2 English as a Foreign Language students preparing for high-stakes examinations such as CEFR and IELTS. A mixed-methods research design was employed, combining a quasi experimental classroom study involving 12 participants divided into control and experimental groups with a comprehensive diagnostic survey of 18 language learners. The experimental group received strategic scaffolding consisting of thematic visual anticipation, contextualized lexical activation, and AI-generated transcript decoding via specialized fill-in-the-gaps tasks targeting paraphrased options. Empirical findings reveal that this structured framework significantly mitigated core testing impediments, particularly the challenge of navigating deceptive distractor choices. Survey data corroborated the experimental success, indicating a substantial upward shift in post intervention student performance and affective confidence levels. The results suggest that explicit strategy instruction combined with systematic, AI-assisted pedagogical task design effectively equips learners with the necessary micro-skills to navigate complex multi-choice assessment frameworks.